2021
DOI: 10.3390/nu13020313
|View full text |Cite
|
Sign up to set email alerts
|

Are Dietary Indices Associated with Polycystic Ovary Syndrome and Its Phenotypes? A Preliminary Study

Abstract: Polycystic ovary syndrome (PCOS) is a complex hormonal disorder which impairs ovarian function. The adherence to healthy dietary patterns and physical exercise are the first line of recommended treatment for PCOS patients, but it is yet unclear what type of diet is more adequate. In this case-control study, we explored associations between adherence to five dietary quality indices and the presence of PCOS. We enrolled 126 cases of PCOS and 159 controls living in Murcia (Spain). Diagnostic of PCOS and its pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 84 publications
(95 reference statements)
2
10
0
4
Order By: Relevance
“…In contrast, Zhang B. et al in 2020 found no difference between the three study groups (a group of women with PCOS and oligo-ovulation, a group of women with PCOS and normal ovulation, and a group of healthy women without PCOS) in alcohol consumption patterns [ 43 ]. Similar findings were published by Sánchez-Ferrer et al in 2020 and Cutillas-Tolín et al in 2021, showing no differences in alcohol consumption patterns between a group of women with PCOS and a group of healthy women [ 44 , 45 ]. However, all the cited studies differ significantly in methodology, did not use the AUDIT test, and only asked about drinking alcohol.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Zhang B. et al in 2020 found no difference between the three study groups (a group of women with PCOS and oligo-ovulation, a group of women with PCOS and normal ovulation, and a group of healthy women without PCOS) in alcohol consumption patterns [ 43 ]. Similar findings were published by Sánchez-Ferrer et al in 2020 and Cutillas-Tolín et al in 2021, showing no differences in alcohol consumption patterns between a group of women with PCOS and a group of healthy women [ 44 , 45 ]. However, all the cited studies differ significantly in methodology, did not use the AUDIT test, and only asked about drinking alcohol.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the investigators further reported marked differences in the habitual dietary behaviours between the two groups, whereby women with PCOS consumed less EVOO, legumes, fish/seafood, and nuts compared to women without PCOS. In corroboration with the aforementioned study, Cutillas-Tolín et al [78] reported that adherence to a MedDiet was protective against clinical phenotypic features of PCOS, namely hyperandrogenism and oligo-anovulation. Moreover.…”
Section: Discussionsupporting
confidence: 70%
“…We previously reported that PCOS women had lower adherence to the MD as compared with BMI-matched controls, with an inverse association among the adherence to MD, BMI, and the clinical severity of the disease [81]. Accordingly, Cutillas-Tolín A et al (2021) [82] found that the women with PCOS and a higher adherence scores to the MD had a lower BMI. In our study, we confirmed that a low adherence to the MD was very common among MUO-PCOS, as up to 85% of MUO-PCOS had a PREDIMED score <5.…”
Section: Discussionmentioning
confidence: 91%